Lumberjanes. Volume eighteen, Horticultural horizons - Watters, Shannon; Leyh, Kat (Boom! Box, 2021)
After getting in trouble with Rosie, the director of Miss Qiunzella Thiskwin Penniquiqul Thistle Crumpet's Camp for Hardcore Lady Types, the members of the Roanoke cabin are tasked with getting firewood for the campfire. While doing so, they discover a journal chronicling the origin of the Lumberjanes. Meanwhile, a mysterious creeping vine starts to take over camp, and the group encounters Rosie's ex-best friend Abigail once more.